Training Of Trainer (Tot) Perencanaan Mitigasi Bencana Untuk Staff Happy Heart - Rudy Pramono; Chandra Han (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2020)
Indonesia is a country in the path of the most active earthquake in the world. The disaster prone condition is caused because Indonesia is in the Pacific ring of fire and is on top of three continental plates colliding. Disaster management training should be a priority for disaster-prone areas. With a wide area coverage, training to prepare trainers to be able to handle disasters is very important. The Happy Heart Foundation's efforts in collaboration with Pelita Harapan University hold community service activities in West Nusa Tenggara with the Training of Trainer (TOT) Disaster Mitigation Planning program is very important to assist disaster mitigation planning. This activity was held at Arrahman Elementary School, Kecinan Hamlet, Malaka Village, Pamenang Sub District, District North. Lombok, Nusa Tenggara which suffered severe damage from the earthquake on August 15, 2018. The school building damaged by the impact of the earthquake was completed by the Happy Heart Foundation in 2019. This TOT is expected to be able to produce competent trainers to plan for disaster mitigation. The number of participants was 5 people and was carried out in two days with a variety of comprehensive methods ranging from lectures, discussions, simulations, computer practices to field practice. Based on the evaluation conducted in general, the training took place well and was useful for participants to support the disaster preparedness school program at the school that had been built by Happy Heart, which is generally located in disaster prone areas.